Ibalizumab and Fostemsavir in the Management of Heavily Pre-Treated HIV-infected Patients - Riccardi, Niccolò; Berruti, Marco; Del Puente, Filippo; Taramasso, Lucia; Di Biagio, Antonio (Recent Patents on Anti-Infective Drug Discovery, 2018)
Background: Heavily treated HIV-1 infected patients may have limited therapeutic alternatives. In order to ensure sustained HIV-RNA suppression in these patients and to improve current antiretroviral treatment regimens in the fight against multi-drug resistant strains, new drugs are needed. Recently, two new drugs among the new generation of entry inhibitors showed promises for both their characteristics and mechanism of action. Objective: To outline ibalizumab (Patent: US20120121597A1) and fostemsavir (Patent: US8871771) future applications in people living with multi-drug resistant HIV with few remaining treatment options. Methods: We analysed the available literature and data from ongoing clinical trials about ibalizumab and fostemsavir. Results: Ibalizumab is a new humanized monoclonal antibody. It acts as post-attachment inhibitor by binding CD4 2nd domain of T lymphocyte and preventing HIV connection to CCR5 or CXCR4 and has been recently approved by Food and Drug Administration in the United States of America as a new intravenous antiretroviral agent for heavily treated HIV adults with multi -drug resistant infection. Fostemsavir (formerly BMS-663068), the oral prodrug of temsavir, is another attachment inhibitor. It acts by preventing the viral connection to CD4 by binding gp120. This drug showed encouraging results in heavily treated patients as add-on agent to current antiretroviral regimens, in particular for subtype B virus. It is currently being investigated in a phase 3, two-cohort (randomized and non-randomized), trial. Conclusion: The history of ibalizumab and fostemsavir will be written in next years. Continuing the research will be crucial to obtain evidence based guidelines for the management of heavily treated HIV-1 infected patients with limited therapeutic options.
Keywords: heavily pre-treated patients